PENERAPAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS SAINS BUDAYA LOKAL DI SEKOLAH DAN MADRASAH - Mansir, Firman; Purnomo, Halim; Tumin, Tumin (TARBAWY : Indonesian Journal of Islamic Education, 2020)
Abstract. This article examines the application of science and culture-based Islamic Education at school and madrasa. This research refers to application of natural science which is related to the Indonesian local culture by giving priority to the values in Islam. This research aims to search for and research about the applied science by pairing or linking it with Indonesian culture. In its process, this research is not directing the learning of Islamic Religious Education to either the Â qualitative, quantitative or mix of them, but this learning can use one or even both of them in its learning methodology. This research discusses the application of learning that leads to science and refers to Indonesian culture by considering at Islamic values. It can be referred to as observations of habits taught and practiced in the learning process activities in schools and madrasas.Â Abstrak. Artikel ini mengkaji penerapan pembelajaran Pendidikan Agama Islam di sekolah dan madrasah yang berbasis sains dan budaya. Penelitian ini mengarah kepada penerapan sains atau ilmu pengetahuan alam yang dikaitkan dengan budaya lokal di Indonesia khususnya dengan mengutamakan nilai-nilai yang ada di dalam Islam. Tujuan dari penelitian ini adalah untuk mencari dan meneliti tentang ilmu sains yang diterapkan dengan menyandingkan atau mengkaitkan dengan budaya Indonesia. Dalam prosesnya, penelitian ini bukan mengarahkan pembelajaran Pendidikan Agama Islam pada ranah kualitatif dan kuantitatif atau penggabungan namun pembelajaran ini bisa menggunakan salah satu bahkan kedua-duanya dalam metodologi pembelajarannya. Kajian ini membahas penerapan pembelajaran yang mengarah pada sains dan kebudayaan Indonesia dengan melihat nilai-nilai keislaman. Hal it dapat disebut sebagai hasil pengamatan kebiasaan yang diajarkan dan dipraktekkan pada kegiatan proses pembelajaran di sekolah dan madrasah.